ECONOMIC ASPECTS OF IMPLEMENTING RENEWABLE ENERGY SOURCES AS A MEANS OF OPTIMIZING THE RESTORATION OF ELECTRICITY NETWORKS - KHOROSHY, YAROSLAV; NETREBSKYY, VOLODYMYR; MALOGULKO, YULIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article examines the economic aspects of implementing renewable energy sources (RES) in Ukraine as a strategic tool for restoring and stabilizing electricity networks under wartime conditions. Following large-scale damage to the national energy infrastructure, the role of RES has shifted from environmental priorities to ensuring energy security and resilience. The study outlines the dynamics of renewable generation in Ukraine, where the installed capacity declined from 9.9 GW in 2021 to 8.7 GW in early 2024, yet investment activity in solar and wind power continues despite the war. The research emphasizes that the existing “green tariff” model, while effective in the 2010s, has led to territorial imbalances, concentrating generation in southern regions most affected by hostilities. To address this, the authors propose a differentiated regional tariff mechanism that adjusts incentives according to the electricity deficit or surplus in specific regions. Such an approach would redirect investment flows to areas with high consumption but limited generation, thus reducing regional disparities, improving grid reliability, and advancing decentralization of the energy system. The article compares Ukraine’s situation with European and global practices, highlighting Germany’s and China’s experience with regionally adjusted tariffs and quota mechanisms. The proposed model anticipates multiple benefits: increased investor interest in less favorable regions, growth of local bioenergy projects, improved public acceptance, reduction of transmission losses, and stimulation of smart grids and energy storage systems. At the same time, the authors stress the importance of regulatory predictability, transparent rules, and integration with network modernization to mitigate risks of overcapacity or curtailment. Overall, the differentiated green tariff is presented as a pragmatic economic instrument that could accelerate Ukraine’s transition to decentralized, sustainable, and secure energy development, while simultaneously contributing to regional resilience and post-war recovery.
Keywords: renewable energy sources; energy; tariff; investments